2016
DOI: 10.1039/c5ce02340h
|View full text |Cite
|
Sign up to set email alerts
|

Superlattice-like SnSb4/Ge thin films for ultra-high speed phase change memory applications

Abstract: Superlattice-like (SLL) SnSb4/Ge thin films were studied by thermal, electrical and optical methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 24 publications
2
9
0
Order By: Relevance
“…The total durations of the crystallization and amorphization processes of the [S4(30)− S1(20)] 1 thin film are 4.9 and 3.7 ns, respectively, both being much faster than those of GST (17.7 ns for crystallization and 16.5 ns for amorphization). 17 This fast phase change speed of the [S4(30)−S1(20)] 1 thin film has also been realized in the device test, as demonstrated in Figure 1d. The PCM cells were fabricated using 0.18 μm CMOS technology.…”
Section: Resultssupporting
confidence: 62%
“…The total durations of the crystallization and amorphization processes of the [S4(30)− S1(20)] 1 thin film are 4.9 and 3.7 ns, respectively, both being much faster than those of GST (17.7 ns for crystallization and 16.5 ns for amorphization). 17 This fast phase change speed of the [S4(30)−S1(20)] 1 thin film has also been realized in the device test, as demonstrated in Figure 1d. The PCM cells were fabricated using 0.18 μm CMOS technology.…”
Section: Resultssupporting
confidence: 62%
“…The difference for E g is related to the carrier concentration. Since the carrier density inside the semiconductors is proportional to expfalse(Eg/2KTfalse) [13]. A broad band gap will increase the obstacle of carrier transition, leading to the reduction of carriers.…”
Section: Resultsmentioning
confidence: 99%
“…However, some aspects limit its application in PCM, such as the low activation energy (2.24 eV for the phase change from the crystal to rock salt structure) [8, 9], the great density change (6.8% from amorphous to NaCl‐type crystal state) [10], high RESET current (>1 mA) [11] and the long crystallisation time (∼100 ns) [11]. It is reported that Sb‐rich phase change material has fast switching speed due to its growth‐dominated crystallisation mechanism, such as Ge–Sb [12], Sn–Sb [13] and Cu–Sb–Te [14]. At the same time, Te element is harmful to semiconductor technology due to its volatilisation [15].…”
Section: Introductionmentioning
confidence: 99%
“…However, the phase-change speed of GST is relatively low, and its thermal stability, especially amorphous stability, is unsatisfactory. 8,9 Superlattice-like (SLL) PCM materials have attracted much attention in recent years because of better thermal stability 10 and rapid crystallization speed 11 because of their modulated multilayer structure. The GeTe/Sb 2 Te 3 SLL structure-based interfacial phase-change memory device showed improved cycle lifetimes and switching speeds.…”
Section: Introductionmentioning
confidence: 99%
“…Chalcogenides such as Ge–Sb–Te-based compounds are typical materials in rewritable optical media and in nonvolatile electronic memory devices, with Ge 2 Sb 2 Te 5 (GST) being one of the most widely used compositions. However, the phase-change speed of GST is relatively low, and its thermal stability, especially amorphous stability, is unsatisfactory. , Superlattice-like (SLL) PCM materials have attracted much attention in recent years because of better thermal stability and rapid crystallization speed because of their modulated multilayer structure. The GeTe/Sb 2 Te 3 SLL structure-based interfacial phase-change memory device showed improved cycle lifetimes and switching speeds. , The main goal currently is to further refine the synthesis of SLL thin films and master the solid-state reaction to attain specific desired properties.…”
Section: Introductionmentioning
confidence: 99%